2017
DOI: 10.1055/s-0037-1598199
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Continuous Two-Team Approach in Autologous Breast Reconstruction

Abstract: Autologous breast reconstruction has been noted in the literature to provide superior aesthetic outcomes and patient satisfaction. Additionally, free perforator flap tissue transfer has the potential for lower abdominal donor site morbidity. However, it has been noted that the percentage of women who are undergoing autologous breast reconstruction in the United States is decreasing. Factors related to the technical difficulty, prolonged operative times, and decreasing reimbursement have been implicated as the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
71
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(78 citation statements)
references
References 15 publications
3
71
0
Order By: Relevance
“…A study has demonstrated co-surgeon approach safely decreases operative times and reduces physician fatigue and burnout. 17 This study also demonstrated that take-back procedures performed during the weekend by a covering surgeon are associated with a higher rate of flap loss. This "weekend effect" is inconclusive in the literature.…”
Section: Discussionmentioning
confidence: 53%
“…A study has demonstrated co-surgeon approach safely decreases operative times and reduces physician fatigue and burnout. 17 This study also demonstrated that take-back procedures performed during the weekend by a covering surgeon are associated with a higher rate of flap loss. This "weekend effect" is inconclusive in the literature.…”
Section: Discussionmentioning
confidence: 53%
“…While implementation of the CST remains low (14.1%, n = 76), almost one‐third of nonusers expressed interest in future use (31.1%, n = 145), citing potential time and cost savings, as well as the opportunity for mentorship and learning new techniques. In other surgical areas, reports of cosurgeon approaches for complex and/or bilateral procedures describe benefits of time‐ and cost‐savings, improved efficiency, reduced complications, decreased fatigue/burnout, and decreased blood loss/transfusion rates …”
Section: Discussionmentioning
confidence: 99%
“…In other surgical areas, reports of cosurgeon approaches for complex and/or bilateral procedures describe benefits of time-and cost-savings, improved efficiency, reduced complications, decreased fatigue/burnout, and decreased blood loss/transfusion rates. [9][10][11][12] Reimbursement for cosurgeon surgeries is often less than 100% for the second surgeon. At our institution, second surgeon reimbursement from BM cases is 60%-80% of the primary surgeon reimbursement.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies, which included a mixed cohort of unilateral and bilateral MBRs showed reduced operative times, but were inconclusive about the impact of the CSs on complications perhaps because of a small sample size (i.e., underpowered). 15,16 A study from Sweden, which looked only at unilateral delayed breast reconstructions demonstrated a reduction in OR time but had an incomplete evaluation of postoperative complications. 14 Other surgical specialties have evaluated the CSM for lengthy and/or technically demanding procedures with similar benefits.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13] This topic has also been explored in delayed breast reconstructions and a mixed cohort of unilateral/bilateral mastectomies. [14][15][16] The aim of the current study is to evaluate the impact of the CSM specifically on bilateral microsurgical breast reconstruction (MBR). The hypothesis is CS compared with single surgeon (SS) procedures reduces operative time and surgical complications.…”
mentioning
confidence: 99%